2010
DOI: 10.1128/iai.00190-10
|View full text |Cite
|
Sign up to set email alerts
|

Detailed In Vivo Analysis of the Role of Helicobacter pylori Fur in Colonization and Disease

Abstract: Helicobacter pylori persistently colonizes the harsh and dynamic environment of the stomach in over one-half of the world's population and has been identified as a causal agent in a spectrum of pathologies that range from gastritis to invasive adenocarcinoma. The ferric uptake regulator (Fur) is one of the few regulatory proteins that has been identified in H. pylori. Fur regulates genes important for acid acclimation and oxidative stress and has been shown to be important for colonization of H. pylori in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 65 publications
(87 reference statements)
0
40
0
2
Order By: Relevance
“…Also, like the Che Ϫ mutant defect, the fur defect is less significant in the corpus. Fur regulates some chemotaxis genes, such as cheV1, possibly explaining the overlapping phenotypes (13,33). Thus, these three bacterial properties affect corpus-antrum localization in different ways and suggest that normal H. pylori variations might influence stomach region density.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, like the Che Ϫ mutant defect, the fur defect is less significant in the corpus. Fur regulates some chemotaxis genes, such as cheV1, possibly explaining the overlapping phenotypes (13,33). Thus, these three bacterial properties affect corpus-antrum localization in different ways and suggest that normal H. pylori variations might influence stomach region density.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that different H. pylori strains achieve higher bacterial colonization numbers in either the corpus or the antrum (1,27,33). For example, strain X47 has a strong preference for the corpus, and strain SS1 has an antral preference or colonizes the antrum and corpus equally, depending on the study (1,27,47).…”
mentioning
confidence: 99%
“…The vast majority of these studies have focused on resistance to various stressful environments (10,18,27,60), identification of the regulon of genes controlled by each regulatory factor (16, 17, 19-21, 23, 61), or elucidation of the contribution of each regulator to colonization in an animal model (8)(9)(10)(11). Despite the evidence supporting the fact that the Fur, NikR, and ArsRS regulons show considerable overlap, very few studies (8,17,25,53) have attempted to analyze the combined effect of these regulatory factors in H. pylori biology.…”
Section: Discussionmentioning
confidence: 99%
“…Three key nodes within this regulatory structure are represented by the following regulatory proteins: Fur, the ferric uptake regulator; NikR, a nickel response regulator; and ArsRS, an acid-responsive two-component system (7). The prominent roles of these regulators are highlighted by the fact that all three are required for wild-type colonization levels in animal models (8)(9)(10)(11). The importance of the OmpR-like response regulator ArsR is further demonstrated by the fact that it is essential for in vitro survival.…”
mentioning
confidence: 99%
“…Although substitution mutations at the Fur R88 position are not found commonly in H. pylori isolates from humans, an R88H mutation identical to the mutation observed in the present study has been detected in at least three H. pylori isolates from humans (57). Previous studies have shown that H. pylori Fur has a role in resistance to high-salt conditions (49) and resistance to oxidative stress (50-54) and contributes to H. pylori colonization of the stomach (58). To further investigate the functional consequences of the Fur-R88H mutation, we compared the abilities of H. pylori strains producing either WT Fur or Fur-R88H to grow in medium containing elevated salt concentrations or in oxidative-stress environments.…”
Section: Figmentioning
confidence: 50%